Empirical examination of the relationship between supply chain effectiveness and a company's overall success - Prashanth Nagendra Bharadwaj (Administrative Sciences, 2024)
The relationship between the effective management of supply chains and overall organizational success is not fully explained in the literature. The differences in the effectiveness of supply chains as well as the corporate social responsibility (CSR) of supply chain companies in North America, Europe, and Asia Pacific are not broadly studied. This article attempts to bridge that gap in the literature using data from the Gartner Supply Chain Group, Brand Finance, American Consumer Satisfaction Index, and Bloomberg Finance. Pertinent statistical tools including multiple regression, ANOVA, t-tests, and chi-square tests were utilized in the study. SCM top performers were found to have higher customer satisfaction than their industry counterparts; supply chain variables used currently do not have a statistically significant impact on the overall success of those companies; North American companies have experienced significantly higher supply chain effectiveness than their counterparts in Europe and Asia Pacific; and European supply chain companies are significantly ahead of companies in America and Asia in the area of CSR. The findings can help managers in companies to benchmark with their global peers. The main contribution of this research is that it demonstrates the value of supply chain effectiveness while underscoring the need for further research to link supply chain effectiveness with organizational performance. Supply chain managers need to explore operational or internal process metrics that have a more significant impact on overall company success.
Keywords: 350; supply chain effectiveness; customer satisfaction; brand value; corporate social responsibility; market capitalization; inventory turns; return on assets